Producer Attitudes Toward Groundwater Conservation in the U.S. Ogallala‐High Plains. Issue 4 (6th October 2019) - Lauer, Stephen; Sanderson, Matthew R.
Abstract: We present descriptive findings on attitudes towards groundwater conservation and management from a survey of 1, 226 producers farming in the High Plains/Ogallala aquifer region of the United States. We find that a super‐majority of producers agree that groundwater should be conserved rather than entirely depleted. The majority perceives groundwater depletion to be a serious problem. Producers perceive depletion to be a greater problem for their communities than for their own farming operations. There is overwhelming agreement that groundwater should be conserved for altruistic reasons to benefit future generations in the community. Most producers believe they have limited personal capacity for additional groundwater conservation on their farms, and few are involved in voluntary group conservation initiatives. We suggest that a key element of the conservation challenge is social and that future efforts should focus on developing networks, capacities, and cultures of groundwater conservation on the High Plains.